Interventions on fruit and vegetable intake in low-, middle-, and high-income countries: A scoping review of evidence and knowledge gaps - Azupogo, Fusta; Koyratty, Nadia; Smith, Taryn J.; Hinnouho, Guy-Marino; Tharaney, Manisha; Bliznashka, Lilia; Amunga, Dorcas A.; Angeles-Agdeppa, Imelda; Goyena, Eva; Grant, Frederick; Kinabo, Joyce; Mitchodigni, Irene Medeme; et al. (SAGE Publications, 2025)
Background Adequate fruit and vegetable (F&V) intake is important for health, yet populations globally are failing to meet recommendations.